168 Effects of proportion of pigs per feeder hole and stocking density on growth performance and tail and ear biting in the nursery - Laskoski, Fernanda (J Anim Sci, 2019)
The objective of this study was to evaluate the impact of different numbers of pigs per feeder hole and stocking densities on growth performance and incidence of tail and ear biting in the nursery. A total of 2,160 pigs (PIC 337 × Camborough, initial BW 6.1 ± 0.3 kg; weaning age 21.5 ± 0.7 d) were used in a 42-d study. Each pen contained a semi-automatic feeder with 2, 4, 6, or 8 holes of 16 cm wide by 14 cm deep each. At allotment, 20 pigs were placed per pen. The experiment was designed in a 4 x 3 factorial arrangement with nine replicates per treatment, comparing four different number of pigs per feeder hole (PFH) (10; 5; 3.3 and 2.5), and three stocking densities (SD) (0.15; 0.25 and 0.35 m(2)/pig). Pen was the experimental unit for data analysis. For final weight and ADG, a quadratic effect (P = 0.001) was observed for PFH and linear effect (P = 0.001) for SD. For ADFI, low stocking density increased ADFI (linear, P = 0.002). For G:F, a quadratic effect was observed for PFH (P = 0.037). No significant effects were observed for mortality (P > 0.464). The percentage of removals was affected by the interaction between PFH and SD (P = 0.039), indicating that increasing feeder space may reduce the percentage of removals at high stocking densities (0.15 and 0.25 m(2)/pig). For tail and ear biting, a quadratic effect was observed for PFH and SD (P = 0.031). These results suggest that both feeder space and stocking density affect performance and incidence of tail and ear biting, most of the times as quadratic and linear effects, respectively, and the factors may work together to influence pig removal rate in the nursery phase. [Image: see text]